Altered Protein Expression of Cardiac CYP2J and Hepatic CYP2C, CYP4A, and CYP4F in a Mouse Model of Type II Diabetes-A Link in the Onset and Development of Cardiovascular Disease? - Benoit Drolet; Sylvie Pilote; Carolanne Gélinas; Alida-Douce Kamaliza; Audrey Blais-Boilard; Jessica Virgili; Dany Patoine; Chantale Simard (MDPI AG, 2017)
Arachidonic acid can be metabolized by cytochrome P450 (CYP450) enzymes in a tissue- and cell-specific manner to generate vasoactive products such as epoxyeicosatrienoic acids (EETs-cardioprotective) and hydroxyeicosatetraenoic acids (HETEs-cardiotoxic). Type II diabetes is a well-recognized risk factor for developing cardiovascular disease. A mouse model of Type II diabetes (C57BLKS/J-db/db) was used. After sacrifice, livers and hearts were collected, washed, and snap frozen. Total proteins were extracted. Western blots were performed to assess cardiac CYP2J and hepatic CYP2C, CYP4A, and CYP4F protein expression, respectively. Significant decreases in relative protein expression of cardiac CYP2J and hepatic CYP2C were observed in Type II diabetes animals compared to controls (CYP2J: 0.80 ± 0.03 vs. 1.05 ± 0.06, n = 20, p < 0.001); (CYP2C: 1.56 ± 0.17 vs. 2.21 ± 0.19, n = 19, p < 0.01). In contrast, significant increases in relative protein expression of both hepatic CYP4A and CYP4F were noted in Type II diabetes mice compared to controls (CYP4A: 1.06 ± 0.09 vs. 0.18 ± 0.01, n = 19, p < 0.001); (CYP4F: 2.53 ± 0.22 vs. 1.10 ± 0.07, n = 19, p < 0.001). These alterations induced by Type II diabetes in the endogenous pathway (CYP450) of arachidonic acid metabolism may increase the risk for cardiovascular disease by disrupting the fine equilibrium between cardioprotective (CYP2J/CYP2C-generated) and cardiotoxic (CYP4A/CYP4F-generated) metabolites of arachidonic acid.